Surgical Management of Cavernous Malformations Presenting with Drug-Resistant Epilepsy - Alonso-Vanegas, Mario A.; Cisneros-Franco, Jose Miguel; Otsuki, Taisuke (Frontiers in Neurology, 2012)
Cerebral cavernous malformations (CM) are dynamic lesions characterized by continuous size changes and repeated bleeding. When involving cortical tissue, CM pose a significant risk for the development of drug-resistant epilepsy, which is thought to be result of an altered neuronal network caused by the lesion itself and its blood degradation products. Preoperative evaluation should comprise a complete seizure history, neurological examination, epilepsy-oriented MRI, EEG, video-EEG, completed with SPECT, PET, functional MRI and/or invasive monitoring as needed. Radiosurgery shows variable rates of seizure freedom and a high incidence of complications, thus microsurgical resection remains the optimal treatment for CM coursing with drug-resistant epilepsy. Two thirds of patients reach Engel I class at three-year follow-up, regardless of lobar location. Those with secondarily generalized seizures, a higher seizure frequency, and generalized abnormalities on preoperative or postoperative EEG, show poorer outcomes, while factors such as gender, duration of epilepsy, lesion size, age, bleeding at the time of surgery, do not correlate consistently with seizure outcome. Electrocorticography and a meticulous removal of all cortical hemosiderin –beyond pure lesionectomy– reduce the risk of symptomatic recurrences.